PENGARUH PRODUK DAN PROMOSI TERHADAP KEPUASAN NASABAH TABUNGAN SISWA PADA KSP “RIAS” P1.MARDIHARJO KABUPATEN MUSI RAWAS - Suwarno Suwarno (LPPM UNIVERSITAS BINA INSAN, 2016)
The results of the data analysis and discussion described in the previous chapter, the following conclusions can be drawn: There is a significant influence between the product and promotion of customer satisfaction Student Savings (TASIS) in the